Investigating food limitations in wild fisheries: the attendance and growth responses of fish at an anthropogenic feeding station within a temperate estuary. Issue 2 (23rd June 2020) - Cook, Denham G.; Jaksons, Peter; Jerrett, Alistair
Abstract: To investigate whether wild fish populations are food limited, this study explored whether the provision of supplementary food had a positive effect on the abundance, condition and growth characteristics of estuarine fish assemblages in New Zealand. Feed (7690 kg) was delivered from an anthropogenic feeding station over a 60‐week period to a naturally occurring assemblage of wild fish. Yellow‐eyed mullet ( Aldrichetta forsteri ) of juvenile, sub‐adult and newly matured size classes were the dominant species actively foraging at the feeding station throughout its operation, whereas larger piscivorous species visited and foraged from the feed station over the summer period only. Other species were present in the wider area of Nelson Haven, but not at the feed station. No obvious changes in the condition factor of yellow‐eyed mullet were observed across the period of monitoring, and no changes in their catchability were detected – although marked seasonal variation in catch rates was observed. Results from tag‐recapture data identify that the length‐based growth rates of yellow‐eyed mullet recaptured near the feed station were higher than those of tagged individuals recaptured at a nearby comparison site, and were higher than the growth rates observed in natural populations of yellow‐eyed mullet in the wider region. Shifts in the median size of fish, as observed by acoustic observations, agreed with the tag‐recapture data. Although some of the results identified were not amenable to statistical analyses, the attendance of yellow‐eyed mullet at the feeding station, in combination with the improved estimates of growth by most of the techniques employed, indicates that yellow‐eyed mullet are food limited in their natural environment and that the growth performance of these fish can be positively affected by the increased availability of food.